Dim and Small Target Detection Based on Improved Bilateral Filtering and Gaussian Motion Probability Estimation - Fan Xiangsuo; Qin Wenlin; Feng Gaoshan; Huang Qingnan; Min Lei (IEEE Photonics Journal)
Dim and small target detection plays an important role in infrared target recognition systems. In this paper, we present a dim and small target detection algorithm based on improved bilateral filtering and Gaussian motion probability estimation, aiming to improve the detection efficiency of the detection system. First, a bilateral filtering algorithm based on image patch analysis is proposed to complete the background modeling, compare with single pixel, image patch contains more neighborhood information. Then, we use the Gaussian process combining the target position of consecutive $n$ frames to predict the target position of the $(n+1)\text{th}$ frame, and the target energy is accumulated along the trajectory direction at the same time. Finally, we construct the grayscale probability model to realize the multi-frame correlation detection, which combining the grayscale features and the motion characteristics of the target. Six scenes and eleven comparison algorithms are selected for experiments, experimental results show the effectiveness and robustness of the proposed algorithm.